Exploration of sodium lactate as the draw solute of forward osmosis for food processing. (May 2021) - Xiao, Shengjian; Li, Zihe; Xiong, Qinmei; Wu, Chongde; Huang, Jun; Zhou, Rongqing; Jin, Yao
Abstract: This work explored the feasibility of sodium lactate as a novel draw solute to conduct the forward osmosis (FO) process in the field of food processing. As a common low-cost food addictive, sodium lactate is non-toxic and shows high osmotic pressure. Based on this knowledge, the results of this work further revealed the combinative effect of osmotic pressure and viscosity of sodium lactate solution on the FO performance. The effect of draw solution concentration, membrane orientation and temperature on the FO performance were also investigated. The results revealed that a maximal average water flux of 56 LMH was reached during the FO experiments with sodium lactate as draw solute. Taking into account the average water flux and the reverse solute flux, 7.1 M was the optimal concentration of the sodium lactate solution for FO process. The application of such draw solution into the concentration of sugar solution and orange juice then validated its promising performance in terms of efficiency, food quality preservation and membrane regeneration. Highlights: Sodium lactate solution can be a proper draw solution for food processing. FO performance using sodium lactate solution was systematically assessed. A combinative effect of osmotic pressure and viscosity of draw solution was revealed. FO using sodium lactate showed high ability for food quality preservation.